The role of sociocultural factors on physical fitness in PON-achieving students from watershed area schools - Mikdar, Ujen Zenal; Wahyudi, Arief Nur; Perdana, Jeff Agung (Jurnal Cakrawala Pendidikan, 2025)
Sociocultural factors can contribute to the level of physical fitness. This study aims to determine the level of students’ physical fitness and the role of sociocultural influences. This research design uses a mix-method explanatory approach that produces quantitative data and is reinforced by qualitative data. The sampling technique was purposive sampling, and the sample of this study was 30 students with achievements in the National Sports Week (PON) who attended schools in the watershed area. The average results of male students' physical fitness data are in the good category (48.27 ml/kg/min), and female students' physical fitness is also in the good category (36.65 ml/kg/min). This condition is supported by the sociocultural roles experienced by students. The sociocultural roles include those of coaches who are firm, disciplined, measured, and motivating; self-awareness of the value of leading a healthy lifestyle, which is reinforced by parents who actively remind and set an example; social support from family and friends; and the influence of the sociocultural environment, which includes local-specific physical activities like farming, hunting, and driving a "jukung" to school. The role of the government provision of infrastructure and facilities in the home and school environment, and the role of teachers who provide extracurricular activities, as well as cultural traditions such as dance and martial arts, have a role in shaping their physical fitness.